Whistleblowers, Media and the Law: Challenges in Combating Corruption - Mat Rus, Mukhriz; Ahmad, Normahfuzah; Ahmad Tekmezi, Ahmad Shahriman (2023)
The Rasuah Busters Campaign is a society-led initiative to combat corruption. The campaign is primarily headed by a team of private media experts from Karangkraf and their sub-divisions such as Sinar Harian to play a pivotal media role in raising public awareness on issues of corruption in the country. Part of their effort in raising and reporting on issues of corruption includes the enhancement to the protection of whistleblowers in Malaysia. This paper seeks to analyse the relevant laws governing whistleblowers and investigative journalism in preventing and combating corruption in particular the Whistleblower Protection Act (2010). It also investigates the challenges faced by whistleblowers in speaking out on corruption cases and other misconduct from the perspective of Karangkraf, particularly the Rasuah Busters team and Sinar Harian. This socio-legal study combines doctrinal legal and qualitative methodology in analysing the legal text and contexts based on primary and secondary data. The study utilizes in-depth interviews with, among others the Rasuah Busters team. Findings indicate there is a need to revise the current legislation with regard to the conception and protection of whistleblowers. Additionally, a cultural revamp is needed among the public on corruption cases. Finally, effective news media reporting is only feasible through independent and free media on which the public can rely upon.